2002
DOI: 10.1002/nla.285
|View full text |Cite
|
Sign up to set email alerts
|

The solvability conditions for inverse eigenproblem of symmetric and anti‐persymmetric matrices and its approximation

Abstract: SUMMARYThe problem of generating a matrix A with speciÿed eigen-pair, where A is a symmetric and antipersymmetric matrix, is presented. An existence theorem is given and proved. A general expression of such a matrix is provided. We denote the set of such matrices by SAS n E . The optimal approximation problem associated with SAS n E is discussed, that is: to ÿnd the nearest matrix to a given matrix A * by A ∈ SAS n E . The existence and uniqueness of the optimal approximation problem is proved and the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In [5,[16][17][18] it is shown that S(Z, ) is nonempty if and only (Z, ) satisfies certain conditions involving Moore-Penrose inverses or singular value decompositions of matrices related to (Z, ). However, no method is given for choosing pairs (Z, ) that satisfy the conditions and, because of the restricted spectral structures of the matrices in question, it is not likely that a randomly chosen (Z, ) will be admissible.…”
Section: Problem 1 (Inverse Eigenproblem)mentioning
confidence: 98%
See 1 more Smart Citation
“…In [5,[16][17][18] it is shown that S(Z, ) is nonempty if and only (Z, ) satisfies certain conditions involving Moore-Penrose inverses or singular value decompositions of matrices related to (Z, ). However, no method is given for choosing pairs (Z, ) that satisfy the conditions and, because of the restricted spectral structures of the matrices in question, it is not likely that a randomly chosen (Z, ) will be admissible.…”
Section: Problem 1 (Inverse Eigenproblem)mentioning
confidence: 98%
“…Recently the following problems have received attention [5,[16][17][18]. These references describe applications in which such problems arise.…”
Section: Introductionmentioning
confidence: 98%
“…On this topic of PDIEPs, the earlier study can be found for real symmetric Toeplitz matrices [1,13] and Jacobi matrices in [1,14], and some of the recent works can be found for anti-symmetric matrices in [15], anti-persymmetric matrices in [16], centrosymmetric matrices in [17], symmetric anti-bidiagonal matrices in [18], K-symmetric matrices in [19], and K-centrohermitian matrices in [12]. This is by far not a complete list, see [2] for a recent review, a number of applications and an extensive list of references.…”
Section: Introductionmentioning
confidence: 97%
“…They also occur in a remarkable variety of applications [2,[5][6][7][8] and have been studied for different classes of structured matrices. We refer the reader to [9][10][11][12] and references therein. For example, Zhou et al [10] and Zhang et al [12] considered the problems for the case of centro-symmetric matrices and Hermitian-generalized Hamiltonian matrices, respectively.…”
Section: Introductionmentioning
confidence: 99%